1998
DOI: 10.1002/cjce.5450760608
|View full text |Cite
|
Sign up to set email alerts
|

Greffage de molécules à la surface du silicium par voie électrochimique

Abstract: La surface hydrogenee du silicium possede des proprietes remarquables, mais une stabilite a I'oxydation insuffisante. Pour y remedier, plusieurs groupes organiques ont ete substitues a I'hydrogene de surface. Ces greffages peuvent se fairc chimiquement en plusieurs etapes, mais la voie electrochimique permet des reactions directes a partir de la surface hydrogenee. On peut ainsi methoxyler partiellement la surface du silicium poreux par dissolution anodique controlec, mais surtout methyler sa surface de manier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The nanoscale architecture of porous silicon is inherently fragile, and thus rapid and efficient syntheses under room-temperature conditions are preferable. Previous approaches taken toward Si−C bond formation on porous silicon include reactions with methyl Grignard under electrochemical conditions, alkyl and aryllithium and Grignard reagents in the absence of electronic bias, and thermal hydrosilylation of alkynes and alkenes . We have found that hydrosilylation of unsaturated carbon−carbon bonds on the native hydride-terminated porous silicon can be induced by the Lewis acid EtAlCl 2 or white light illumination (on photoluminescent samples) at room temperature in a matter of minutes or hours, depending upon the organic fragment, as outlined in Scheme .…”
Section: Introductionmentioning
confidence: 95%
“…The nanoscale architecture of porous silicon is inherently fragile, and thus rapid and efficient syntheses under room-temperature conditions are preferable. Previous approaches taken toward Si−C bond formation on porous silicon include reactions with methyl Grignard under electrochemical conditions, alkyl and aryllithium and Grignard reagents in the absence of electronic bias, and thermal hydrosilylation of alkynes and alkenes . We have found that hydrosilylation of unsaturated carbon−carbon bonds on the native hydride-terminated porous silicon can be induced by the Lewis acid EtAlCl 2 or white light illumination (on photoluminescent samples) at room temperature in a matter of minutes or hours, depending upon the organic fragment, as outlined in Scheme .…”
Section: Introductionmentioning
confidence: 95%
“…Chazalviel and co-workers [27][28][29] were the first to propose the use of Grignard salts on both porous and flat silicon, under electrochemical conditions [30]. Bansal et al [31] showed that it is possible to chlorinate the H-Si(1 1 1) surface in a benzene solution of PCl 5 , which in principle allows to further react the obtained chlorinated surface with organic Grignard reagents.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Similar reactions have been reported for modification of porous silicon. [13][14][15][16][17] In addition, covalently modified surfaces also may be prepared from the reaction of alkyl Grignard or alkyllithium reagents with the halogenated Si(111) surface. [18][19][20][21] In many of these examples the reactions lead to organic films that are terminated with a methyl group.…”
mentioning
confidence: 99%
“…While this is useful for passivation and chemical stabilization, the low reactivity of the terminal methyl group makes further manipulation of the surface physical or chemical properties difficult. Other workers have demonstrated the possibility of creating a functionalized organic film on a single crystal 4,[11][12][13][14]22 surface, but only in a few cases have the sequential reactions of the organic film been investigated. 2,3,6 To incorporate more complex organic or bioorganic structures at the interface new strategies to increase the chemical functionality of the surface must be devised.…”
mentioning
confidence: 99%